STRUCTURE OF FINITELY GENERATED VIRTUALLY SEMISIMPLE MODULES OVER COMMUTATIVE RING - Wandiansyah
Simple and semisimple modules are one of the most important classes of modules in module theory and also in their application.On 2016, Mahmood Behboodi et al. introduced virtually simple modules and virtually semisimple modules which is a generalization of semisimple modules . A Virtually semisimple module is a nonzero module where each submodules is isomorphic with a direct summand of that module. While a virtually simple module is a module in which each submodules is isomorphic to that module. In this thesis discusses some basic properties of virtually simple modules and virtually semisimple modules, besides that it is also proven that ifM is a finitely generated modules over commutative ring R dan RM is a virtually semisimple module tehen RM = Ln i=1 R=Pi with R=Pi a principal ideal domain